FBGA solder ball defect effect on DDR4 data signal rise time and ISI measured by loading the data line with a capacitor. (November 2020) - Waqar, Muhammad; Baeg, Sanghyeon; Bak, Geunyong; Kwon, Junhyeong; Lee, Kiseok; Jeon, Sang Hoon
Abstract: This paper proposes a new method of investigating the effect of void or fracture in FBGA solder ball on the DDR4 data signal rise time and inter-symbol interference (ISI), by loading the data line with a capacitor. A void or fracture in solder ball increases its capacitance which effects the data signal rise time and increases ISI. For measuring ISI large consecutive patterns of 1's or 0's followed by a changing bit are used. However in in-field systems it is not possible to run large patterns of 1's or 0's. So the data line is loaded with a 0.2 pF capacitive load on a UDIMM test card to mimic the increased capacitance due to FBGA solder ball void defect of height 0.2 mm and cross sectional area of 0.0045 mm 2 . The loaded line shows increase in rise time of 16 ps. For loaded line the data eye opening is 0.077 UI lesser. This decrease in data eye means more ISI and will cause increase in intermittent errors. Highlights: Proposes a new method of investigating the effect of void or fracture in FBGA solder ball A capacitor is loaded on the DDR4 data line to mimic the effect of FBGA fault Rise time of the data signal with capacitive load shows increase Channel loss of the data line with capacitive load shows increase hence more intermittent errors